An Analysis of Japanese Verb Conjugation Errors Among Students at Universitas Harapan Medan - Yusuf, Muhammad; Taulia; Mawaddah, Alvy (Abdul Media Literasi, 2024)
This study aims to identify and analyse the common verb conjugation errors among students in the Japanese Language Program at Universitas Harapan Medan. The research method utilised was the analysis of student essays, focusing on verb conjugation forms such as te, ta, nai, and nakatta. The collected data indicates that the most frequent errors occur in the te and ta forms, accounting for 43.37% and 42.17%, respectively. These findings suggest that students struggle with differentiating between positive and negative past forms. Errors in the negative forms nai and nakatta were also found at lower percentages. The results of this study indicate a need to improve the teaching methods of verb conjugation at the university.